Changes in composition of envelope proteins in adenylate cyclase- or cyclic AMP receptor protein-deficient mutants of Escherichia coli. - Aono, R (1978)
Synthesis of several envelope proteins in Escherichia coli K-12 is regulated by cyclic AMP and cyclic AMP receptor protein.